Guideline Adherence for Intrapartum Group B Streptococci Prophylaxis in Penicillin-Allergic Patients - Kimberly A. Paccione; Harold C. Wiesenfeld (Hindawi Limited, 2013)
Objective. To investigate adherence to the 2002 Centers for Disease Control and Prevention (CDC) guidelines for perinatal group B streptococci (GBS) prevention in penicillin-allergic obstetric patients. Methods. This is a retrospective cohort study of penicillin-allergic obstetric patients who tested positive for GBS and delivered at our institution in 2010. Electronic medical records were reviewed for the nature of the penicillin allergy, documentation of having previously tolerated cephalosporins, gestational age at delivery, type of delivery, antimicrobial sensitivity testing, and antibiotics administered. Antimicrobial sensitivity testing and "appropriate" antibiotic choice, which was determined using 2002 CDC guidelines, were analyzed. Results. Intrapartum antibiotic prophylaxis was administered in 97.8% (95% confidence interval [CI] 93.5-99.5%) of patients, but it was considered appropriate in only 62.2% (95% CI 53.8-70.0%) of patients. Clindamycin was the most commonly used antibiotic, but 26.4% (95% CI 16.3-39.7%) of patients who received clindamycin did not have confirmation of susceptibility via antimicrobial sensitivity testing. Overall, the sensitivity testing was performed in only 65.5% (95% CI 56.2-73.7%) of patients in whom it was indicated. Conclusion. Compliance with CDC guidelines for performing antimicrobial sensitivity testing and choosing an appropriate antibiotic in GBS-positive penicillin-allergic women continues to be suboptimal. Institution of measures to increase adherence is necessary.